Dynamics of a Stochastic Multigroup SEIR Epidemic Model - Xiaojing Zhong; Feiqi Deng (Journal of Applied Mathematics)
To be more precise about the real world activity, a stochastic multigroup SEIR epidemic model is formulated. we define the basic reproduction number R0S and show that it is a sharp threshold for the dynamics of SDE model. If R0S<1, the disease-free equilibrium is asymptotically stable; and if R0S>1, the disease persists and there exists a globally asymptotically stable stationary distribution. Numerical simulation examples are carried out to substantiate the analytical results.